Acute intoxication caused by synthetic cannabinoids 5F-ADB and MMB-2201: A case series. (April 2017) - Barceló, Bernardino; Pichini, Simona; López-Corominas, Victoria; Gomila, Isabel; Yates, Christopher; Busardò, Francesco Paolo; Pellegrini, Manuela
Highlights: Synthetic cannabinoids have recently been present in the Spanish drug market. Five young patients with intoxication by synthetic cannabinoids are described. They presented with psychomotor agitation, confusion, anxiety and psychosis. Three of them believed to be possessed and have super powers. 5F-ADB, MMB-2201 and their metabolites were identified by UHPLC–MS/MS in urine. Abstract: Synthetic cannabinoids are relatively new substances of abuse. Recently, abuse of synthetic cannabinoids has been increasingly reported in the lay press and medical literature. When new compounds are introduced, their use is initially not restricted by prohibition therefore their consumption cannot be verified by standard drug tests. The use of these compounds among adolescents and young adults is constantly growing, making it important for emergency services to be familiar with the signs and symptoms of intoxication present. Overdose and chronic use of these substances can cause adverse effects including altered mental status, tachycardia, and loss of consciousness. Here, we report five cases of acute intoxication by synthetic cannabinoids 5F-ADB and MMB-2201 with analytical confirmation.